Evaluation of a Suitable Extractant and Determination of Critical Limit of Boron in Soil and Mustard (Brassica Juncea L.) Plant by Various Extractants in Inceptisols of Varanasi. Issue 10 (31st May 2017) - Yadav, Shobh Nath; Singh, S. K.; Kumar, Omkar; Latare, A. M.; Kumar, Manish
ABSTRACT: Pot culture experiment was conducted to evaluate the suitability of extractants and to determine the critical limit of boron (B) in soil and mustard plant in Inceptisols of Varanasi. Twenty-one bulk soil collected from different locations were used for growing mustard. Five extractants, namely hot water, hot 0.01molar (M) calcium chloride (CaCl2 ), 0.01M CaCl2  + 0.05 M mannitol, 1.0 M ammonium acetate (NH4 OAC) and 0.05 M hydrochloric acid (HCl), were assessed by correlating the amount of extractable B in untreated and B fertilizer-treated soil with Bray's per cent yield, plant tissue B concentration and B uptake by mustard. Similarly, correlation coefficients of the B extracted by different extractants and soil properties were calculated. The suitability of B extracted by different extractants was in the order of hot 0.01M CaCl2 (HCC-B) > hot water (HW-B) > 1.0 M NH4 OAC (AA-B) > 0.05M HCl (HA-B) > 0.01M CaCl2  + 0.05M mannitol (CCM-B). The critical limits of extractable B in soil as determined by the graphical procedure were 0.54, 0.60, 0.36, 0.45 and 0.45 mg kg −1 and the statistical procedures were 0.54, 0.60, 0.38, 0.46 and 0.48 mg kg −1 with HW-B, HCC-B, CCM-B, AA-B and HA-B, respectively. Soil containing available B below the critical limit responded to B fertilization.